1999
DOI: 10.1093/bja/83.3.415
|View full text |Cite
|
Sign up to set email alerts
|

Desflurane and isoflurane improve neurological outcome after incomplete cerebral ischaemia in rats

Abstract: We have investigated the effects of isoflurane and desflurane on neurological outcome in a rat model of incomplete cerebral ischaemia. We studied 40 non-fasted male Sprague-Dawley rats, anaesthetized, intubated and ventilated mechanically with isoflurane and nitrous oxide in oxygen (FlO2 0.3). Arterial and venous catheters were inserted for measurement of arterial pressure, drug administration and blood sampling. A biparietal electroencephalogram (EEG) was recorded continuously using subdermal platinum electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(42 citation statements)
references
References 22 publications
1
35
0
6
Order By: Relevance
“…9 The concentration of 1.5% isoflurane equals 1.0 minimum alveolar anesthetic concentration. 15,16 To exclude the possible influence of hypotension, hypothermia, or respiratory depression on the beneficial effects of isoflurane, we measured the physiological variables during isoflurane pretreatment. The results showed no obvious changes in physiological variables during isoflurane preconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…9 The concentration of 1.5% isoflurane equals 1.0 minimum alveolar anesthetic concentration. 15,16 To exclude the possible influence of hypotension, hypothermia, or respiratory depression on the beneficial effects of isoflurane, we measured the physiological variables during isoflurane pretreatment. The results showed no obvious changes in physiological variables during isoflurane preconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…k or no effect Not determined Koorn et al (1993); Toner et al (2002) k k or no effect Engelhard et al (1999), Mackensen et al (1999), Halothane No effect Not determined Koorn et al (1993); Toner et al (2002) Sevoflurane k or inconsistent effect…”
Section: Isofluranementioning
confidence: 99%
“…Dans nombre d'études, la neuroprotection anesthésique a été confirmée chez le rat soumis à une ischémie hémisphérique focale ou complète; dans ces études, l'administration d'isoflurane, de sévoflurane, de desflurane et de xénon, ainsi que de barbituriques et de propofol, a réduit la taille de l'infarctus et amélioré les fonctions motrice et cognitive lorsqu'elle avait lieu avant l'exposition à l'ischémie. [5][6][7][8][9] Il a été montré que la réduction de la lésion neuronale ischémique était le plus importante dans des modèles d'étude comparant l'état « anesthésié » à des états éveillé ou sous sédation et Nous ne savons pas si les effets des agents anesthésiques observés dans ces différents modèles d'ischémie sont permanents. Les études menées sur des rats soumis à une ischémie cérébrale focale ou globale incomplète ont montré que la mort cellulaire était considérablement réduite dans la période suivant immédiatement l'ischémie; toutefois, aucune différence n'a été observée dans les lésions corticales et sous-corticales dans les semaines ou mois suivants.…”
Section: Resultsunclassified
“…In numerous studies, anesthetic neuroprotection has been confirmed in rodents subjected to focal or incomplete hemispheric ischemia where isoflurane, sevoflurane, desflurane, and xenon, as well as barbiturates and propofol, decreased infarct size and improved motor and cognitive function when given prior to the ischemic challenge. [5][6][7][8][9] The reduction in ischemic neuronal injury has been shown to be most prominent in study designs comparing ''anesthesia'' with awake or sedated states and less pronounced when different anesthetics were compared with each other. Neurologic outcome is reproducible only with brief episodes of cerebral ischemia, while longer durations of low-flow states or permanent focal ischemia are resistant to anesthetic neuroprotection.…”
mentioning
confidence: 99%